Jambi City Diskominfo's (Dinas Komunikasi dan Informasi) Public Service Communication Strategy Through the Jambi City SiKesal (Sistem Informasi Keluhan Masyarakat Online) Application in 2021 - Lamone, Diego; Sofyan, Nur (Jogjakarta Communication Conference (JCC), 2023)
Communication strategies need to be planned and implemented optimally to improve the quality of public services and build good coordination in carrying out public services. The purpose of this study was to find out the public service communication strategy of DISKOMINFO in Jambi City through the SiKesal application for Jambi City in 2021. This study used a qualitative research method with a case study approach with interview and documentation data collection techniques. The results of this study show that the Jambi City Diskominfo implements strategic communication according to the planning, implementation, and evaluation stages. This study shows the results of how the communication strategy can affect the goals that have been set. Diskominfo aims to provide maximum public services and get satisfaction from the community; it can be proven that all reports from the people of Jambi City through the SiKesal application in 2021 have been successfully responded to.